B5. A cross comparison study of USCOM® and transthoracic echocardiography in pregnancy. (12th August 2016) - Vinayagam, D.; Patey, O.; Thilaganthan, B.; Khalil, A.
Abstract: Introduction : There is a paucity of data regarding the accuracy, reliability and reproducibility of non-invasive cardiac output monitors in pregnancy. The aim of this study was to compare cardiac output estimations obtained by USCOM® against those obtained by two-dimensional transthoracic echocardiography (TTE). Methods : Prospective, observational study in which 114 healthy pregnant and postpartum women had haemodynamic indices obtained by USCOM® and TTE. Accuracy and precision statistics (Bland Altman analysis) are presented as bias, precision, 95% limits of agreement (LOA) and mean percentage difference (MPD). Intraobserver repeatability and interobserver reproducibility of USCOM was assessed in 67 and 40 subjects respectively. Results : USCOM® had a positive bias ranging from 0.4 to 0.9 L/min. The MPD of USCOM® was 28% in the third trimester cohort, which meets the current level of <30% for clinical acceptability. However, we found no agreement in the first, second trimester or postpartum groups (MPD of 38%, 38% and 44% respectively). We found excellent repeatability (ICC = 0.969, 95% CI 0.953–0.980) and reproducibility (ICC= 0.896, 95% CI 0.812–0.944) for USCOM®. Conclusions : We have demonstrated clinically acceptable agreement between USCOM® and TTE in the third trimester of pregnancy. Future studies should consider developing USCOM®-specific reference ranges in pregnancy and the postpartum period.